Recreational park in Selangor / Norlaila Ahmad Fahmi - Ahmad Fahmi, Norlaila (2005)
Forest is important to human, animals and fauna itself Apart from providing shelter and foods, it acts as water catchments area and provides the environmental stability. The establishment of recreational forest is to reduce and minimizes deforestation. It also established as part of government step in maintaining the world stability. The study of recreational park is conducted in Selangor. The area of study is at the Kanching Recreational Forest, The Commonwealth Forest Park and Sungai Tua Recreational Forest. The data used is from secondary data that provided by Jabatan Perhutanan Selangor. The rivers, waterfalls and distance from residential area are among the factor that attracts visitors. By keeping up with maintaining the facilities and giving enough promotion, number of visitors can be increased.